2020
DOI: 10.3390/cancers12082028
|View full text |Cite
|
Sign up to set email alerts
|

Primary Thromboprophylaxis in Ambulatory Pancreatic Cancer Patients Receiving Chemotherapy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Patients with pancreatic cancer (PC) carry the highest risk of venous thromboembolism (VTE) amongst all cancer patients. Appropriate use of primary thromboprophylaxis might significantly and safely reduce its burden. We performed a systematic review of published studies and meeting abstracts using MEDLINE and EMBASE through July 2020 to evaluate the efficacy and safety of primary thromboprophylaxis in ambulatory PC patients receiving chemotherapy. The Mantel–Haenszel random effect model was used to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…Another meta-analysis including a heterogeneous group of ambulatory cancer patients treated with LMWH showed a reduction in VTE incidence by 49% (95% CI, 0.43-0.56) with no significant increase in MB. 25 This study also reported a significant VTE reduction with thromboprophylaxis in PDAC-specific patient population (odds ratio, 0.26; 95% CI, 0.14-0.48) similar to the results from Tun et al 25 An updated meta-analysis of PATP in ambulatory patients with PDAC by Frere et al, 26 also demonstrated that PATP significantly reduced the risk of VTE (pooled RR, 0.31 [95% CI, 0.19-0.51; P < 0.00001, I 2 = 8%]; absolute risk difference, −0.08 [95% CI, −0.12 to −0.05; P < 0.00001, I 2 = 0%]), with an estimated NNT of 11.9 patients to prevent one VTE event.…”
Section: Systematic Review and Meta-analysessupporting
confidence: 72%
“…Another meta-analysis including a heterogeneous group of ambulatory cancer patients treated with LMWH showed a reduction in VTE incidence by 49% (95% CI, 0.43-0.56) with no significant increase in MB. 25 This study also reported a significant VTE reduction with thromboprophylaxis in PDAC-specific patient population (odds ratio, 0.26; 95% CI, 0.14-0.48) similar to the results from Tun et al 25 An updated meta-analysis of PATP in ambulatory patients with PDAC by Frere et al, 26 also demonstrated that PATP significantly reduced the risk of VTE (pooled RR, 0.31 [95% CI, 0.19-0.51; P < 0.00001, I 2 = 8%]; absolute risk difference, −0.08 [95% CI, −0.12 to −0.05; P < 0.00001, I 2 = 0%]), with an estimated NNT of 11.9 patients to prevent one VTE event.…”
Section: Systematic Review and Meta-analysessupporting
confidence: 72%
“…They conclude that there is evidence that thromboprophylaxis could provide clinical benefit for patients during chemotherapy, but additional trials are necessary to determine the exact type of anticoagulant as well as dosage, duration etc. [36] This conclusion is supported by the review of Mulder et al discussing international guidelines for thromboprophylaxis in cancer patients. [37] However, in the current study, most VTEs (51 out of 64, 80%) occurred in the advanced phase of disease in which patients no longer received any medical treatment.…”
Section: Discussionmentioning
confidence: 88%
“…By contrast, VTE has a high recurrence rate, and anticoagulation is associated with bleeding events, including gastrointestinal bleeding [ 14 , 25 ]. Recently, a meta-analysis of 1003 pancreatic cancer patients has revealed that anticoagulation therapy significantly reduced the risk of symptomatic VTE without increasing major bleeding [ 26 ]. Considering these results, the International Initiative on Thrombosis and Cancer (14) and American Society of Clinical Oncology Clinical Practice [ 25 ] guidelines recommend anticoagulation therapy with apixaban or rivaroxaban in cancer outpatients undergoing chemotherapy with a Khorana score ≥ 2, no bleeding risk and no drug-drug interactions (Grade 1B) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%